Wild capuchin monkeys spontaneously adjust actions when using hammer stones of different mass to crack nuts of different resistance. Issue 1 (2nd May 2016) - Liu, Qing; Fragaszy, Dorothy M.; Visalberghi, Elisabetta
ABSTRACT: Objectives: Expert tool users are known to adjust their actions skillfully depending on aspects of tool type and task. We examined if bearded capuchin monkeys cracking nuts with stones of different mass adjusted the downward velocity and the height of the stone when striking palm nuts. Materials and Methods: During a field experiment carried out in FBV (Piauí, Brazil), eight adult wild capuchin monkeys (five males) cracked Orbygnia nuts of varied resistance with hammer stones differing in mass. From recorded videos, we identified the highest strike per nut‐cracking episode, and for this strike, we calculated the height to which the monkey lifted the stone, the maximum velocity of the stone during the downward phase, the work done on the stone, and the kinetic energy of the strike. Results: We found that individual capuchins achieved average maximum kinetic energy of 8.7–16.1 J when using stones between 0.9 and 1.9 kg, and maximum kinetic energy correlated positively with mass of the stone. Monkeys lifted all the stones to an individually consistent maximum height but added more work to the stone when using lighter stones. One male and one female monkey lifted stones higher when they cracked more resistant nuts. The high resistance of the Orbygnia nut elicits production of maximum kinetic energy, which the monkeys modulate to some degree by adding work to lighter stones. Discussion: Capuchin monkeys, like chimpanzees, modulate their actions in nut‐cracking, indicating skilled action, although neither species regulates kinetic energy as precisely as skilled human stone knappers. Kinematic analyses promise to yield new insights into the ways and extent to which nonhuman tool users develop expertise. Am J Phys Anthropol 161:53–61, 2016. © 2016 Wiley Periodicals, Inc.